2001
DOI: 10.1097/00006534-200105000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Breast Reconstruction with SalineFilled Implants: No Interference with the Oncologic Outcome?

Abstract: The possible adverse effects on cancer control due to immediate breast reconstruction have been addressed recently for both silicone-filled implants and flap reconstruction. To evaluate those possible effects after immediate breast reconstruction with saline-filled implants, 49 patients reconstructed with saline-filled breast implants at the Jules Bordet Cancer Institute were studied. Selection was only based on the possibility to find a matched patient. These patients were matched with a control group of 49 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 9 publications
2
25
0
3
Order By: Relevance
“…The goal of postmastectomy breast reconstruction is to restore the appearance of the breast and to improve psychological outcomes after cancer ablation. [35][36][37][38] Thus, the assessment of patient outcomes using appropriately constructed and validated instruments is essential to evaluate and quantify the success of these surgeries from the patient's perspective. 39,40 By using specific patient-reported measures, such as the BREAST-Q, the HADS (for measuring general distress), and the IES (for capturing cancer-specific distress), we have analyzed Hr-QOL and satisfaction data in a prospective cohort of 55 patients who underwent free MS-TRAM or DIEP flap breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of postmastectomy breast reconstruction is to restore the appearance of the breast and to improve psychological outcomes after cancer ablation. [35][36][37][38] Thus, the assessment of patient outcomes using appropriately constructed and validated instruments is essential to evaluate and quantify the success of these surgeries from the patient's perspective. 39,40 By using specific patient-reported measures, such as the BREAST-Q, the HADS (for measuring general distress), and the IES (for capturing cancer-specific distress), we have analyzed Hr-QOL and satisfaction data in a prospective cohort of 55 patients who underwent free MS-TRAM or DIEP flap breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of studies, radiotherapy is shown to adversely affect outcome after implant-based breast reconstructions, with increased late failure rates (5,11,12), poor aesthetic results, loss of symmetry (13)(14)(15), capsular contracture, and infection, even when using the latest generation of implants (5,11,12,14,(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: The Effect Of Radiotherapy On Breast Reconstructionmentioning
confidence: 99%
“…Studies addressing the safety of IBR have shown varying rates of local recurrence [17][18][19][20][21][22][23][24][25][26]. As there may be a considerable interval before recurrences occur, confirmation of these results requires a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%